Iatrogenic rectal injury during radical prostatectomy: Is colostomy inevitable end? - Topaktaş, Ramazan; Erdem, Mehmet Remzi; Polat, Emre Can; Ersöz, Cevper; Önol, Şinasi Yavuz (Derman Medical Publishing, 2016)
Aim: Radical prostatectomy (RP) is the gold standard treatment method for localized prostate cancer, because of its high oncological success. Iatrogenic rectal injury (IRI) during RP is rarely seen, but it may causes serious complications because of the close anatomic relationship between the prostate and rectum. Aim is to present our series about management of IRI without colostomy. Material and Method: Between June 1999 and June 2013, radical retropubic prostatectomy (RRP) was performed to 372 patients by a single surgeon. 10 cases (% 2,6) were complicated by a rectal injury during RRP. Instant rectal closure was performed in 3 layers without a diverting colostomy, at the time of surgery. Omental vascular flap was placed between rectum and vesicourethral anastomosis. Results: The clinical stages of IRI cases were T1c, T2a and T2c in 2, 3 and 5 patients, respectively. Their preoperative Gleason scores were 6, 7 and 8 in 3, 5 and 2 patient, respectively. None of the 10 had undergone previous prostatic or rectal surgery, or received preoperative radiotherapy or hormonal therapy. Discussion: Instant diagnosis and rectal wall closures by three layers are essential for successful repair. Our technique seems as a safe, minimal invasive and highly effective option for the management of IRI.

Amaç: Lokalize prostat kanserinde, radikal prostatektomi yüksek onkolojik başarısı nedeniyle altın standart tedavi metodudur. Radikal prostatektomi sırasında iyatrojenik rektal yaralanma (İRY) nadiren görülür fakat bu durum prostat ve rektumun anatomik yakın ilişkisinden dolayı ciddi komplikasyonlara sebep olabilir. Amacımız kolostomisiz tedavi ettiğimiz iyatrojenik rektal yaralanma serimizi sunmaktır. Gereç ve Yöntem: Haziran 1999 ve Haziran 2013 yılları arasında aynı cerrah tarafından retropubik radikal prostatektomi (RRP) uygulandı. RRP sırasında 10 vakada (%2,6) rektal yaralanma oldu. Cerrahi esnasında fark edilir edilmez kolostomi diversiyonu uygulanmaksızın üç tabaka halinde rektal açıklık kapatıldı. Omental damarlı flep rektum ve vezikoüretral anastomoz arasına yerleştirildi. Bulgular: İyatrojenik rektal yaralanma gerçekleşen vakaların klinik evresi sırasıyla 2 hastada T1c, 3 hastada T2a ve 5 hastada ise T2c idi. Operasyon öncesi Gleason skorları ise sırasıyla 3 hastada 6, 5 hastada 7 ve 2 hastada ise 8 idi. Rektal yaralanma olan 10 hastanın hiçbiri daha önce prostat veya rektum cerrahisi geçirmemiş ve operasyon öncesi radyoterapi ve hormon tedavisi almamıştı. Tartışma: Erken tanı ve rektum duvarının üç tabaka halinde kapatılması başarılı bir tamirin esasını oluşturur. Uyguladığımız yöntem rektal yaralanma tedavisinde güvenilir minimal invaziv ve oldukça etkili bir tedavi seçeneği gibi görünmektedir.
Radikal prostatektomi esnasında rektal yaralanma: Kolostomi kaçınılmaz son mu?
WOS: 000376566800015
Keywords: Prostatectomy; Rectal Injury; Intraoperative Complication; Prostatektomi; Rektal Yaralanma; İntraoperatif Komplikasyon